1987
DOI: 10.1088/0029-5515/27/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Stability conditions for kink and tearing modes in tokamaks

Abstract: The principle of successive current layers is formulated to analyse the stability conditions for kink and tearing modes in tokamaks. Necessary criteria for kink mode stability with and without conducting casing are examined. Comparison theorems are formulated for both kink and tearing modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The predominantly m = 5 peeling mode has a maximum growth rate at q at the boundary of 4.93. The resistive peeling mode is unstable also when the q = 5 surface is just inside the plasma (in agreement with earlier results without a separatrix [17][18][19]). However, the peeling mode is stable for ψ b = 0.998 (CASTOR) and with the full separatrix (JOREK).…”
Section: External Kink (Peeling) Mode In X-point Geometrysupporting
confidence: 92%
“…The predominantly m = 5 peeling mode has a maximum growth rate at q at the boundary of 4.93. The resistive peeling mode is unstable also when the q = 5 surface is just inside the plasma (in agreement with earlier results without a separatrix [17][18][19]). However, the peeling mode is stable for ψ b = 0.998 (CASTOR) and with the full separatrix (JOREK).…”
Section: External Kink (Peeling) Mode In X-point Geometrysupporting
confidence: 92%
“…This is consistent with Ref. 13 where it was shown that adding to the outer region current layers with j 0 eq ðxÞ > 0 degrades the magnetic island stability.…”
supporting
confidence: 92%
“…Later on, using the principle of successive current layers [5,6] and the analytical criteria of stability for the case of homogeneous current density, we shall show that configurations with j = const for p < a, and with a current density decaying to zero for p > ai will be stable in relation to ideal modes even when condition (9) is fulfilled only at the boundary of the…”
Section: W Jomentioning
confidence: 96%
“…region of homogeneity of j(p). Note that fulfilment of condition (9) does not guarantee the stability of tearing modes.…”
Section: W Jomentioning
confidence: 99%
See 1 more Smart Citation